Other-Initiated Self-Repairs in Student-Student Interaction: The Frequency of Occurrence and Mechanism - Putry, Denanda Pratiwi; Munir, Ahmad; Purwati, Oikurema (JEELS (Journal of English Education and Linguistics Studies), 2019)
The current study is intended to explore the typology of other-initiated self-repair in term of its frequency of occurrence and to investigate the mechanism of self-repair in an academic setting. To obtain the required data, a classroom conversational analysis was conducted in which the researchers observed a group of graduate students (19 active EFL speakers) in a state university in East Java, Indonesia. Based on the qualitative data analysis, the results of the study revealed that all typologies of other-initiated selfrepair were used depending on the aims the interlocutors try to gain since all typologies have diverse aims and ways. Of all typologies, confirming checks were dominantly used by the participants. Regarding the mechanisms, three types of mechanisms were found; full two-cycle repair, background check, and short-cut repair sequence.